Association between cerebral small‐vessel disease and Alzheimer's disease pathologies. (31st December 2021) - Cai, Yuan; Mok, Vincent C.T.; Liu, Wanting; Fan, Xiang; Shi, Lin; Au, Lisa W.C.
Abstract: Background: Controversy exists regarding the etiological role of cerebral small vessel disease (CSVD) in Alzheimer's disease (AD). We thus evaluated the association between brain Aβ/tau burden and white matter hyperintensity (WMH) volume among subjects with varying severity levels of cognitive impairment. Method: A total of 84 stroke‐free subjects (healthy controls [HC]=10; subjective cognitive decline [SCD]=32; mild cognitive impairment [MCI]=26; dementia =16) were included. All patients underwent structural MRI, 11C‐ PIB, and 18F‐T807 PET to measure CSVD makers, Aβ deposition (A+) and pathologic tau (T+), respectively. WMH volume was quantified by automatic segmentation using AccuBrain® IV 1.1 (BrainNow Medical Technology Company Ltd.). Result: No significant association was found between A+T+ and WMH volume in the overall population (β =‐0.03 ;95% CI, ‐0.04‐0.11; p=0.10). There was also no significant association found within different cognitive diagnostic group except in those with dementia, where we found that increasing global 11C‐ PIB SUVR correlated with lower WMH volume (B=‐1.76 ;95% CI, ‐2.92‐ ‐0.59; p=0.007). No significant association between 18F‐T807 SUVR and WMH volume was observed Conclusion: We found no association between brain Aβ/tau burden and WMH volume except an inverse association was noted between Aβ and WMH in dementia patients. PiB retention might be restrained by WMH in those patients with higher CSVD burden.